Kajian Kesehatan Hutan dalam Pengelolaan Hutan Konservasi - Rahmat Safe'i; Hari Kaskoyo; Arief Darmawan; Yullia Indriani (ULIN: Jurnal Hutan Tropis, 2020)
Conservation forests must maintain the function and quality of their forests so that the preservation of the living natural resources therein is not damaged and the balance of the ecosystem is well ordered. The benefits of a conservation forest can be felt by the people who live around the forest such as carbon, water sources, non-timber forest products so that the community can prosper. Forest health monitoring is an activity designed to monitor the condition of forest health based on the results of measurable ecological indicators for forest management decision making. The purpose of this study is to determine the value of conservation forest health status and identify internal and external factors of conservation forest health. The method used is Forest Health Monitoring for assessing forest health status and Statistical Product and Service Solutions 20. software for determining the relationship of internal factors with external forest health. The results showed the health status of the conservation forest included in the management area of the Sustainable Peoples Forest System Farmer Group in the Teluk Pandan sub-district of Pesawaran District included in the medium category (3,20) . Internal factors that affect the health of conservation forests are biodiversity and tree damage while external factors that affect the health of conservation forests are the level of farmers' knowledge, farmer participation and farmer motivation.